The Bahamas and the First Extensive Expedition, 1931-1932, of the USDA to the Caribbean Islands - Chavarria, Raquel; Jestrow, Brett; Freid, Ethan; Francisco-Ortega, Javier (International Journal of Bahamian Studies, 2020)
Sponsored by Allison V. Armour and led by David Fairchild, a plant hunting expedition organized by the United States Department of Agriculture (USDA) targeted the Caribbean Islands and the Guianas between December 31, 1931 and April 1, 1932. Three other agriculture scientists joined this plant collecting enterprise: namely, Leonard R. Toy (from University of Florida); and Harold Frederick and Palemon H. Dorsett (both from the USDA). Seven of the Bahamian islands were explored between December 31, 1931 and January 15, 1932 and between March 29 – April 1, 1932. This contribution focuses on the Bahamian itinerary followed during this voyage. Documents and photos housed in the US National Archives, and the Library and Archives of Fairchild Tropical Botanic Garden; herbarium specimens found in the US National Herbarium; and David Fairchild’s published accounts were the basis for our research. A total of 106 plant samples of plants (89 species), including herbarium specimens and material for the USDA were collected in this archipelago. Collections of an unidentified palm grown in the USDA Chapman Field Station, Miami resulted in the description of the Bahamian endemic Coccothrinax inaguensis in 1966 by Robert W. Read. The team failed to collect landraces of sea-island cotton and wild cotton species; even though, that was one of the main priorities for the team. Accounts of this visit were covered by two of Nassau’s newspapers: The Nassau Guardian and The Tribune.